Comprometimento organizacional em grupos semi-autônomos: estudo de caso - Isensee Neto, Juter (2007)
This research searched for evidence, through a case study, of the positive influence exherted by the use of semiautonomous groups in an industry over their workers organizational commitment. The theoretical referential used in this paper was the Socio-Technical theory, along with Fink s (1992) work on the subject of organizational commitment. We used Fink s (1992) research tool, in order to measure the workers commitment in the three aspects defined by the author: job commitment, team commitment and organizational commitment. The field research applied this instrument on two separate groups of workers, working inside the same plant. The first was organized in a more traditional way and the other one used a different setting with semiautonomous worker cells. The major findings obtained from the research were evidences that, in fact, semiautonomous workteams exherted a positive influence towards commitment, mainly within the team commitment and the organizational commitment spheres. In addition to that, in a non-expected bonus result, we were able to find evidence of a negative influence from worker s unions militance over organizational commitment. We suggest that this aspect to be explored in more detail in future works.